A Comprehensive Review of Core Resilience Elements and Indicators: Findings of Relevance to Children and Youth - Liebenberg, Linda; Joubert, Natacha (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2019)
Resilience is core to improving Canadians’ mental health. It is therefore important to expand our understanding of key resilience elements – individuals assets, relational and contextual resources - as they develop throughout the life course; as they relate to Canadian heterogeneity, including Indigenous, immigrant and refugee, African-Canadian and LGBTQ2 communities; and, in the context of chronic/daily stress as well as extreme stress, trauma, violence and marginalised socioeconomic settings. Meaning-making frameworks and processes appear as essential mechanisms in the enactment of personal agency, guiding the use of resilience assets and resources to achieve and maintain positive mental health. This brief report shares findings of a comprehensive literature review, discussing their relevance to children and youth, concluding with implications for related programs and policy.